Paired-Agent Fluorescence Molecular Imaging of Sentinel Lymph Nodes Using Indocyanine Green as a Control Agent for Antibody-Based Targeted Agents. (3rd January 2019) - Li, Chengyue; Xu, Xiaochun; McMahon, Nathan; Alhaj Ibrahim, Omar; Sattar, Husain A.; Tichauer, Kenneth M.
Abstract : Purpose . Paired-agent molecular imaging methods, which employ coadministration of an untargeted, "control" imaging agent with a targeted agent to correct for nonspecific uptake, have been demonstrated to detect 200 cancer cells in a mouse model of metastatic breast cancer. This study demonstrates that indocyanine green (ICG), which is approved for human use, is an ideal control agent for future paired-agent studies to facilitate eventual clinical translation. Methods. The kinetics of ICG were compared with a known ideal control imaging agent, IRDye-700DX-labeled antibody in both healthy and metastatic rat popliteal lymph nodes after coadministration, intradermally in the footpad. Results. The kinetics of ICG and antibody-based imaging agent in tumor-free rat lymph nodes demonstrated a strong correlation with each other ( r  = 0.98, p < 0.001 ) with a measured binding potential of −0.102 ± 0.03 at 20 min postagent injection, while the kinetics of ICG and targeted imaging agent shows significant separation in the metastatic lymph nodes. Conclusion. This study indicated a potential for microscopic sensitivity to cancer spread in sentinel lymph nodes using ICG as a control agent for antibody-based molecular imaging assays.